Relation Macrozoobenthos with Sediment Organic Material in the Intertidal Zone in Selat Baru Beach, Bengkalis Regency, Riau Province - Pramita, Wisnu; Efriyeldi, Efriyeldi; Galib, Musrifin (Journal of Coastal and Ocean Sciences, 2021)
Selat Baru Village was one of several beaches on Bengkalis Island which was located in the northern part of Bengkalis Island. Selat Baru Beach is a tourist spot that has the most visitors every day, especially during the Eid holidays. In addition, there are rivers, ports, and boat crossings also taking place on Selat Baru Beach. The purpose of this study was to determine the content of sediment organic matter, the type and abundance of macrozoobenthos, and to determine the relationship between the organic matter of sediment and the abundance of macrozoobenthos in the New Strait coastal waters. The method used was a survey method, where the data collected was primary data which was then analyzed statistically and discussed descriptively. The results of measurements of oceanographic parameters from the research location have an average temperature of 28,67 oC, and pH of 7, a salinity of 26,33 ‰, transparency of 24,33 cm, and a current velocity of 0,1 m/s. The average sediment content obtained at station 1 was 1,42%, station 2 was 0,77%, and station 3 was 7,34%. The percentage of sand fraction has the highest percentage at station 1 substation 3 (95,56%) and the lowest at station 3 substation 3 (39,78%), while the highest percentage of mud fraction was at station 3 substation 3 (54,19%) and the lowest found at station 2 substation 1 (4,15%). The macrozoobenthos found were from the Bivalvia class (Corbicula sp, Lucinidae sp, Anomia sp) and the Gastropod class (Nucella sp, Rabdotus sp, Cerithidea sp) and the Malacostraca class (Hermigrapsus sp). The average abundance of macrozoobenthos found at station 1 was 4,22 ind/m2, station 2 was 4,22 ind/m2, and station 3 was 10,67 ind/m2. The result shows the effect of the sludge sediment fraction on the abundance of macrozoobenthos has a coefficient of determination (R2) with a value of 0,9015 and a correlation coefficient (r) with a value of 0,9495 meaning that 90,15% of macrozoobenthos abundance was influenced by sediment fraction and the rest was influenced by other environmental factors